2015
DOI: 10.1002/2015ja021516
|View full text |Cite
|
Sign up to set email alerts
|

Substorm simulation: Insight into the mechanisms of initial brightening

Abstract: Initial brightening of the aurora is an optical manifestation of the beginning of a substorm expansion and is accompanied by large‐amplitude upward field‐aligned currents (FACs). Based on global magnetohydrodynamic simulation, we suggest the possible generation mechanism of the upward FAC that may manifest the initial brightening. (1) A formation of the near‐Earth neutral line (NENL) releases the tension force that accelerates plasma earthward. (2) The earthward (perpendicular) flow is converted to a field‐ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
109
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 39 publications
(119 citation statements)
references
References 88 publications
9
109
1
Order By: Relevance
“…It is a general presumption in these models that the onset FACs come from the equatorial plane along a field line. On the contrary, it is shown that the current line deviates from the magnetic field line at off‐equator (Tanaka, ) and that the vortex being responsible for the onset FAC appears at off‐equatorial low‐altitude region (Ebihara & Tanaka, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is a general presumption in these models that the onset FACs come from the equatorial plane along a field line. On the contrary, it is shown that the current line deviates from the magnetic field line at off‐equator (Tanaka, ) and that the vortex being responsible for the onset FAC appears at off‐equatorial low‐altitude region (Ebihara & Tanaka, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ebihara and Tanaka [], hereinafter referred to as Paper 1, dealt with rapid intensification of upward FAC at the beginning of the substorm expansion phase (hereinafter, simply referred to as an initial brightening). Based on the global MHD simulation, they explained the initial brightening as follows: (1) Associated with the development of the convection, a near‐Earth neutral line (NENL) [ Nishida and Nagayama , ; Russell and McPherron , ] releases magnetic tension to compress and accelerate plasma earthward.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been presented that the finer the spatial resolution of the global magnetohydrodynamic (MHD) simulations, which consider the effects of the magnetosphere‐ionosphere (M‐I) coupling, the more realistic the features of the auroral or polar substorms that can be reproduced [ Tanaka et al ., ; Ebihara et al ., ; Tanaka , , hereinafter referred to as Paper 1; Ebihara and Tanaka , , Paper 2; Ebihara and Tanaka , , Paper 3]. In these precise simulations, ionospheric elements of substorms, such as the sudden decrease in the Auroral Lower ( AL ) index, the quiet arc, the dipolarization front, the initial brightening, the westward traveling surge (WTS), the double oval, and the overshielding, are reproduced.…”
Section: Introductionmentioning
confidence: 99%